Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Chapter 4 - Graphs of the Circular Functions - Section 4.4 Graphs of the Secant and Cosecant Functions - 4.4 Exercises - Page 179: 15


$y = csc~(x-\frac{\pi}{4})$ We can see the graph below.

Work Step by Step

$y = csc~(x-\frac{\pi}{4})$ When $x = -\frac{3\pi}{4}$, then $y = csc~(-\pi)$ (which is undefined) When $x = -\frac{\pi}{4}$, then $y = csc~(-\frac{\pi}{2}) = -1$ When $x = \frac{\pi}{4}$, then $y = csc~0$ (which is undefined) When $x = \frac{3\pi}{4}$, then $y = csc~(\frac{\pi}{2}) = 1$ When $x = \frac{5\pi}{4}$, then $y = csc~2\pi$ (which is undefined) We can see the graph below.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.